2015
DOI: 10.3892/mco.2015.529
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of concurrent chemoradiotherapy with S-1 versus weekly cisplatin for locoregionally advanced nasopharyngeal carcinoma

et al.

Abstract: Abstract. This is a prospective randomized trial performed to compare the efficacy of concurrent chemoradiotherapy (CCRT) + S-1 (oral fluoropyrimidine) with that of CCRT + cisplatin in patients with locoregionally advanced nasopharyngeal carcinoma. A total of 105 eligible patients were randomly assigned to receive CCRT with S-1 (S-1 arm, n=50) or cisplatin weekly (control arm, n=55). Patients in the S-1 arm received CCRT plus S-1 (40-60 mg, twice daily for 4 consecutive weeks. Patients in the control arm recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…S-1 is an oral anticancer drug and fluorouracil derivative that can be converted to 5-Fu in vivo, and the advantages of S-1 include its convenient delivery, effectiveness, and mild side effects. 6 The aim of the present study was to investigate the safety and efficacy of low-dose apatinib combined with S-1 as second-line therapy or beyond for NPC with pulmonary and/or hepatic metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…S-1 is an oral anticancer drug and fluorouracil derivative that can be converted to 5-Fu in vivo, and the advantages of S-1 include its convenient delivery, effectiveness, and mild side effects. 6 The aim of the present study was to investigate the safety and efficacy of low-dose apatinib combined with S-1 as second-line therapy or beyond for NPC with pulmonary and/or hepatic metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…S-1 is an oral anticancer drug of fluorouracil derivative and can be converted to 5-Fu in vivo, with the advantages of convenient, efficient, and light side effects. 7 The aim of the study was to investigate whether N3M0 stage NPC treatment could be optimized by concurrent chemoradiotherapy plus S-1 adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…And several studies have demonstrated that S-1 was also effective for nasopharyngeal carcinoma. Wen et al [ 16 ] performed a phase II clinical trial of concurrent chemoradiotherapy with S-1 versus weekly cisplatin for locoregionally advanced nasopharyngeal carcinoma. In this prospective study, the author recruited 105 locally advanced nasopharyngeal carcinoma and randomly divided into chemoradiotherapy plus S-1 group and cisplation group.…”
Section: Discussionmentioning
confidence: 99%